Determinants of the desire to avoid pregnancy after the disaster of the century in Türkiye - Zeliha Özşahin (BMC, 2024)
Abstract Background After natural disasters, the occurrence of mental health problems and adverse effects on reproductive health in women of reproductive age can be attributed to a multitude of factors, including the deterioration of health facilities, a shortage of qualified health professionals, a lack of socio-economic stability, and a paucity of familial and community support. Methods The descriptive correlational study was conducted through social networks with 405 women who had experienced the disaster of the century 8 months after (between November and December 2023) the earthquake. The snowball sampling method was used to obtain the research data. The questionnaire form, developed for the purpose of data collection, was disseminated to women who consented to participate in the study through social networks. The data were evaluated using a variety of statistical techniques, including number, percentage, mean, standard deviation, independent sample t-test, one-way analysis of variance, and structural equation modeling. Results According to the results of linear regression analysis, these were found to be predictors of the desire to avoid pregnancy: having housing problems (β-coefficient 0.173; p = .008), having a damaged home (β-coefficient. 276; p = .009), sleep patterns (β-coefficient 0.433; p = .022), eating habits (β-coefficients 0.248, 0.044), use of psychiatric medication (β-coefficient 0.436, p = .003), and problems related to the food and water supply (β-coefficient 0.127, p = .003). In addition, a structural equation model (SEM) was established to examine the relationship between these variables and mental well-being and pregnancy avoidance. Only the model constructed with mental well-being demonstrated significance in the SEM analysis. Conclusions This study shows that women's mental health is negatively affected in unpredictable emergencies such as earthquakes and that poor mental health negatively affects pregnancy planning. The findings of the study may help to guide health professionals working in the field of women's health to protect women's mental health in emergency situations, to provide counseling about pregnancy planning, and to provide social and psychological support programs.